2016
DOI: 10.1038/srep35887
|View full text |Cite
|
Sign up to set email alerts
|

Efficient recellularisation of decellularised whole-liver grafts using biliary tree and foetal hepatocytes

Abstract: A whole-organ regeneration approach, using a decellularised xenogeneic liver as a scaffold for the construction of a transplantable liver was recently reported. Deriving suitable scaffolds was the first step towards clinical application; however, effective recellularisation remains to be achieved. This report presents a strategy for the improvement of the recellularisation process, using novel cell-seeding technique and cell source. We evaluated recellularised liver grafts repopulated through the portal vein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 25 publications
2
62
0
Order By: Relevance
“…Endothelial cells may enter the extravascular spaces through the altered basement membrane structures that were modified by the decellularization process as detergent‐based decellularization inevitably change/damage the ECM structures . In addition, endothelial cells that were injected to the decellularized liver scaffolds via extrahepatic bile ducts may also enter the extravascular spaces as previously shown . Shear stress has been shown to be an important modulator of endothelial cell morphology .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Endothelial cells may enter the extravascular spaces through the altered basement membrane structures that were modified by the decellularization process as detergent‐based decellularization inevitably change/damage the ECM structures . In addition, endothelial cells that were injected to the decellularized liver scaffolds via extrahepatic bile ducts may also enter the extravascular spaces as previously shown . Shear stress has been shown to be an important modulator of endothelial cell morphology .…”
Section: Discussionmentioning
confidence: 91%
“…33,34 In addition, endothelial cells that were injected to the decellularized liver scaffolds via extrahepatic bile ducts may also enter the extravascular spaces as previously shown. 35 Shear stress has been shown to be an important modulator of endothelial cell morphology. 36,37 It is plausible that these cells may be subject to distinct shear stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal liver cells were seeded through the portal vein and vena cava but showed no accurate distribution of the various differentiated cells to the correct location within the liver lobules. Moreover, Ogiso et al60 demonstrated the existence of organ‐specific cell–ECM communication, which promotes the maturation of engrafted fetal hepatocytes into both hepatocyte and cholangiocyte lineages, without the addition of any prodifferentiation signals. In addition, it was found that using the biliary tree to seed the fetal hepatocytes resulted in a more accurate distribution of differentiated cells as well as an enhanced distribution of hepatocytes into the parenchyma compared to seeding through the vena cava.…”
Section: Decellularized 3d Ecm Scaffolds For Tissue/whole Organ Enginmentioning
confidence: 99%
“…Numerous research projects using various agents to promote partial small liver grafts after LT have been implemented, all of which have only a limited effect for liver graft regeneration . Another approach is a challenging project to make transplantable livers using scaffolding and human embryonic stem cells (PSCs) through a tissue‐engineering technique . Because the structure is 3‐dimensional and several kinds of cells are involved intricately in the liver, projects attempting this approach may require more time.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Another approach is a challenging project to make transplantable livers using scaffolding and human embryonic stem cells (PSCs) through a tissue-engineering technique. 8,9 Because the structure is 3-dimensional and several kinds of cells are involved intricately in the liver, projects attempting this approach may require more time.…”
Section: Introductionmentioning
confidence: 99%